HUBUNGAN DONASI DARAH TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DI UNIT DONOR DARAH PALANG MERAH INDONESIA KABUPATEN BANYUMAS - Novita, Diana; Komsatun A, Komsatun A (Ensiklopedia of Journal, 2020)
Blood donation is the activity of giving / donating blood to be given through a transfusion process to those who need it voluntarily without coercion. This study aims to determine the relationship of blood donation with haemoglobin levels in young women in the Indonesian Red Cross Blood Donation Unit of Banyumas Regency. This research uses descriptive analytic method with approach cross sectional. The sample in this study was 30 young women aged 17 to 25 years and conducted in the Red Cross Blood Donation Unit of Banyumas Regency, Central Java Province. This research was conducted in July 2020. The statistical results of the study are p